Abuso sexual infantil - uma cartografia: silenciamento, testemunho, ressentimento, esquecimento - Camargo, Karina Acosta (2016)
Child sexual abuse – a cartography starts from the author’s body fissures, presenting her own lacerations due to sexual abuses experienced during childhood. This path goes through the issues of silencing, testimony, resentment, forgetfulness, and, lastly, lead – like a birth made through the womb of the earth – to the amor fati. It is a research that aims to overcome the victim-aggressor dichotomy, in order to discuss the complex web that invisibly establishes itself and enables the incitement and the continuity of the sexual abuses, mainly in the family scope. Furthermore, it highlights ways of life invention from the unbearable, excessive and cruel, and art as a possibility of resistance and creation of new ways of existence